Intraventricular Choroid Plexus Cavernoma Resection Using Tubular Retractor System and Exoscope Visualization: A Technical Case Report. Issue 3 (14th March 2022) - Li, Boyi; Kim, Michael G.; Dominguez, Jose; Feldstein, Eric; Kleinman, George; Hanft, Simon
Abstract : BACKGROUND AND IMPORTANCE: Cavernous malformations (CMs) account for approximately 5% to 10% of all CNS vascular malformations, and intraventricular CMs (IVCMs) are a rare subtype, accounting for 2.5% to 10.8% of all intracranial CMs. IVCMs can expand rapidly, leading to compression of adjacent structures, intraventricular hemorrhage, and obstructive hydrocephalus. Diagnosis is challenging because it can mimic a variety of other lesions. CLINICAL PRESENTATION: A 71-year-old man presented after a fall because of imbalance. MRI of the head showed a homogenously enhancing 2-cm mass in the posterior aspect of the right lateral ventricle, with blood layering in the right occipital horn and adjacent parietal edema and leptomeningeal enhancement, as well as a pituitary lesion. DISCUSSION: The patient underwent a right parietal craniotomy for resection of the mass. The ventricle was accessed through a transsulcal approach through the intraparietal sulcus using a tubular retractor system. The mass was arising from the choroid plexus and dissected free in a piecemeal fashion. Postoperative imaging confirmed gross total resection, and the patient had an uneventful recovery. CONCLUSION: Here, we present the first case of a choroid plexus IVCM removed using a tubular retractor system. We demonstrate that this is a safe and effective approach for this rare lesion given the minimal traction on brain parenchyma and enhanced visualization of a deep-seated cavernoma in the lateral ventricle.